Living child-free: proposal for density-dependent regulation in Bewickâ€™s Swans Cygnus columbianus bewickii - Solovyeva, Diana V.; Koyama, Kazuo; Vartanyan, Sergey (Wildfowl, 2019)
Density-dependent population regulation in the Bewickâ€™s Swan Cygnus columbianus bewickii can be assessed from aspects of its productivity including breeding propensity, nest density and clutch size, and also from nest and brood protective behaviour. Bewickâ€™s Swans breeding on the delta of the Chaun River in western Chukotka, Russia, winter in Japan and migrate along Sakhalin Island and the Kolyma River in spring. The flyway population increased > 20-fold from 2,000 to 45,000 individuals between the late 1980s and 2002, and a period of smooth decline or stabilisation was reported thereafter. We collected data on nesting Bewickâ€™s Swans in 2002â€“2018 on Ayopechan Island in the Chaun Delta. There was a negative association between nest density and the number of swans counted in Japan during the January prior to the breeding season (R = â€“0.623, n = 16, P < 0.01), providing evidence for density-dependent population regulation. A mean of 7.9% of all nests were â€œbuilt without layingâ€ in 2014â€“2018. Annual mean clutch size declined significantly by 1.15 eggs, or 23.4% of the initial annual mean, during the study period (F1,14 = 8.89, P < 0.01); year and an integrated spring characteristic (scored from 1 to 3) were the parameters with the greatest influence on clutch size. Nest success was highest (0.92) in aggressive pairs, lower in pairs with â€œnormalâ€ behaviour (0.55), and lowest (0.15) in â€œshyâ€ pairs; these differences in nest success between three behavioural categories were statistically significant (F2,12 = 10.11, P = 0.003). We conclude that the Bewickâ€™s Swan breeding population on the Chaun Delta, and probably along the flyway populationâ€™s breeding range, is regulated by reduced breeding propensity, with declining clutch sizes and low nest success resulting from the behaviour of nesting pairs.